Effect of Injection Bupivacaine Instillation in Gall Bladder Fossa on Post-op Pain Relief after Laparoscopic Cholecystectomy - M. Aslam Rai, M. Fawad Aslam, Sara Aslam (Journal of Rawalpindi Medical College, 2014)
Background: To determine the effect of injection bupivacaine instillation in gall bladder fossa on post-op pain relief after laparoscopic cholecystectomy. Methods: In this randomized controlled trial 80 patients, diagnosed as having gall-stones, were divided into 2 groups for laparoscopic cholecystectomy. Group A received injection bupivacaine instillation in gall-bladder fossa, while Group B did not receive any injection. Results:Out of 40 patients enrolled as bupivacaine group, 30 were female and 10 were male patients with mean age of 45.45 ± 9.86 years, whereas in control group, there were 33 female and 07 male patients in a total of 40 patients, and the mean age was 45.22 ± 11.62 years. Mean VAS scores in bupivacaine group at 8, 16 and 24 hrs were 4.43, 2.98 and 1.35 respectively, while they were 6.30, 3.15 and 1.43 in controls at 8, 16 and 24hrs respectively. VAS scores tended to be higher in females . Need for post-op analgesia in 1st 8hrs was more in the controls(70%). The need for post-op analgesia at 16hrs and 24hrs after surgery was almost equal in both groups. Post-op pain relief in 1st 8hrs was better in the bupivacaine group i.e. 30% vs. 15% . Conclusion: The early post-op VAS scores and pain intensity after 8hrs is decreased with the use of intra-peritoneal instillation of injection Bupivacaine, but it offers no added benefit in terms of post-operative pain relief and need for analgesia post-operatively.